2018
DOI: 10.1002/jrs.5364
|View full text |Cite
|
Sign up to set email alerts
|

Broadband noncollinear optical parametric amplification under low‐frequency picosecond pump in homogeneous KTP crystal

Abstract: The nature of cubic and cascaded quadratic nonlinear responses in the KTiOPO4 crystal under picosecond pump is studied. The main attention is paid to determination of the origin and properties of the blue radiation accompanying the red light amplification process (the central wavelength ~685 nm, bandwidth ~20 nm) in a noncollinear optical parametric amplifier (NOPA) pumped by the second‐harmonic radiation of the picosecond Nd:YAG laser (532 nm). In NOPA, the amplified seed radiation (ωs) becomes so intense tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Vereshchagin and co‐workers described broadband noncollinear optical parametric amplification under low‐frequency picosecond pump in a homogeneous KTP crystal. This phenomenon can be used for effective amplification in picosecond noncollinear optical parametric amplification of weak anti‐Stokes radiation in experiments with time‐resolved broadband picosecond CARS …”
Section: Nonlinear Coherent and Time‐resolved Raman Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Vereshchagin and co‐workers described broadband noncollinear optical parametric amplification under low‐frequency picosecond pump in a homogeneous KTP crystal. This phenomenon can be used for effective amplification in picosecond noncollinear optical parametric amplification of weak anti‐Stokes radiation in experiments with time‐resolved broadband picosecond CARS …”
Section: Nonlinear Coherent and Time‐resolved Raman Spectroscopymentioning
confidence: 99%
“…This phenomenon can be used for effective amplification in picosecond noncollinear optical parametric amplification of weak anti-Stokes radiation in experiments with time-resolved broadband picosecond CARS. [124]…”
Section: Other Coherent Nonlinear Techniquesmentioning
confidence: 99%
“…In Vereshchagin et al [ 11 ] we reported on the observation of a few joint parametric processes resulting in appearance of radiation in spectral ranges of (450–490 nm) and (640–700 nm) at the output of the noncollinear optical parametric amplifier (NOPA). NOPA was based on a homogeneous KTP crystal pumped by picosecond pulses (532 nm, ~63 ps) and seeded by broadband red radiation of a dye modeless laser (~684 nm, bandwidth ~20 nm, ~25 ps).…”
Section: Introductionmentioning
confidence: 99%
“…Along with the basic parametric process of amplifying of the seeding wave, other nonlinear processes of three‐ and four‐wave mixing took place. The work [ 11 ] was devoted to the study of the mechanisms of the appearance in NOPA of radiation with wavelengths shorter than the pump wavelength. The spectral and angular characteristics of radiation in the green–cyan–blue spectral ranges were studied experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Vereshchagin et al studied the nature of the cubic and cascaded quadratic nonlinear responses in a KTiOPO 4 crystal, when it is pumped with picosecond pulses. They observed a variety of linear and nonlinear optical phenomena, which can be utilized in frequency conversion, for instance.…”
mentioning
confidence: 99%